2019
DOI: 10.1051/0004-6361/201833961
|View full text |Cite
|
Sign up to set email alerts
|

Is there a left-handed magnetic field in the solar neighborhood?

Abstract: Context. The analysis of the full-sky Planck polarization data at 850 μm revealed unexpected properties of the E- and B-mode power spectra of dust emission in the interstellar medium (ISM). The positive cross-correlations over a wide range of angular scales between the total dust intensity, T, and both E and (most of all) B modes has raised new questions about the physical mechanisms that affect dust polarization, such as the Galactic magnetic field structure. This is key both to better understanding ISM dynam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 54 publications
2
25
0
Order By: Relevance
“…aanda Another result that extends the recent finding of P18XI is that r T B , and maybe r EB , may indeed differ from zero, with a stronger positive signal at large scale compared to small scales. Bracco et al (2019) suggested that the T B positive correlation at very large scale (for multipoles l < 50) may be principally caused by the Galactic-magnetic field structure in the Solar neighborhood, which would leave an imprint of a left-handed helical component on the T B correlation on scales of a few hundred parsecs. However, at the angular scales probed in this work, other processes may be at play, since for the closest Gould Belt clouds we would be probing physical scales of a few parsecs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…aanda Another result that extends the recent finding of P18XI is that r T B , and maybe r EB , may indeed differ from zero, with a stronger positive signal at large scale compared to small scales. Bracco et al (2019) suggested that the T B positive correlation at very large scale (for multipoles l < 50) may be principally caused by the Galactic-magnetic field structure in the Solar neighborhood, which would leave an imprint of a left-handed helical component on the T B correlation on scales of a few hundred parsecs. However, at the angular scales probed in this work, other processes may be at play, since for the closest Gould Belt clouds we would be probing physical scales of a few parsecs.…”
Section: Discussionmentioning
confidence: 99%
“…Displacing the view point within a kpc-scale shearing box, they found large fluctuations of E-B asymmetry and T -E correlation depending both on the observer's position and on temporal fluctuations of ISM properties due to bursts of star formation. The observer's environment, and the role of the large-scale Galactic magnetic field in the Solar neighborhood, were also considered in Bracco et al (2019) as a possible explanation for the positive T -E and T -B correlations at very low multipoles ( < 50) via a left-handed helical component.…”
Section: Introductionmentioning
confidence: 99%
“…This decomposition yields a field that is parity even, i.e., statistically mirror symmetric, and another one that is parity odd, i.e., statistically mirror antisymmetric (Kamionkowski et al 1997;. The relevant diagnostic quantity is usually the cross correlation of the spectral representations of E and B (Kahniashvili & Ratra 2005;Kahniashvili et al 2014;Bracco et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The alignment of the random GMF around local filaments (including helicity) and non-Gaussianity will be interesting extensions, through which we can study the joint effect of the magnetic field alignment and its spectral anisotropy. In hammurabi X, both the global and local generators are designed to allow in the future the addition of non-Gaussianity, e.g., with the method introduced by Vio et al (2001), helicity, e.g., with the method instructed by Kitaura & Enßlin (2008) and more realistic modeling, e.g., with local filaments studied by Bracco et al (2018). We intend to extend hammurabi X for further studies of Galactic Faraday rotation, dust emission and free-free absorption by including (where possible) the coupling between the random GMF and the thermal electron and dust distributions implemented in similarly calibrated numeric implementations.…”
Section: Discussionmentioning
confidence: 99%